The development and testing of educational game in problem based learning in learning mathemathics. (PBLMath) - Zareena, Rosli (2014)
·Problem Based learning {PBL) is increasingly used in many. disciplines: PBL can be defined as a pedagogocal strategy for posing significance, contextualized, real world situations, providing .. resources, guidance, instruction to learners· as they develop content knowledge and problem solving skills. This research on Problem Based Learning focused on the testing of educational game in Problem Based Learning on Mathematic learning. The objectives of this research is ( l) to evaluate the effectiveness of using game in PBL in term of developing problem solving skills and (2) to evaluate the effectiveness of using PBL in term of students' achievement. The course entitled Engineering Mathematics 2 which covers the Related Rates topic constitutes a compulsary for students in Engineering programmes. Phase one is Analysis which includes literature survey and collection of preliminary analysis data. Second Phase is Designing and Development which adopt ADDIE model as a basis for multimedia development. The last phase is Testing and Evaluation. A total of 53 students involved in this research that are in first year of study from one of Polytechnic in Malaysia The respondent were divided into two groups namely control group and experiment group. Both groups were given a set of pre-test. Three phases involved in this research methodology. There are five research instruments gathered to evaluate the project which are prototype of PBLMath, problem solving sheet, problem solving rubrics, pre-test and post-test questions. The prototype called PBLMath is developed to support the effectiveness of teaching and learning. A t-test was conducted to analysed independent variables by PBL and non PBL treatment while students' problem solving skills and students' achievement are dependent variables. Finding of this study revealed that the students who use game are more competent in (i) identifying diagram and sketches (M=3.88, SD=0.34), (ii) knowing how to use mathematical terminology and notation correctly (M=3.69, SD=0.47) and (iii) connecting logical connections between facts and concepts in mathematics (M=3.63, SD=0.50). Lastly this study has showed that the use of PBL is significantly related to improve students' achievement with the average score of PBLMath group was 73.57 (SD=l5.27) compared to non PBLMath group.